Validation of a Novel Immunoline Assay for Patient Stratification according to Virulence of the Infecting Helicobacter pylori Strain and Eradication Status - Luca Formichella; Laura Romberg; Hannelore Meyer; Christian Bolz; Michael Vieth; Michael Geppert; Gereon Göttner; Christina Nölting; Wolfgang Schepp; Arne Schneider; Kurt Ulm; Petra Wolf; et al. (Journal of Immunology Research)
Helicobacter pylori infection shows a worldwide prevalence of around 50%. However, only a minority of infected individuals develop clinical symptoms or diseases. The presence of H. pylori virulence factors, such as CagA and VacA, has been associated with disease development, but assessment of virulence factor presence requires gastric biopsies. Here, we evaluate the H. pylori recomLine test for risk stratification of infected patients by comparing the test score and immune recognition of type I or type II strains defined by the virulence factors CagA, VacA, GroEL, UreA, HcpC, and gGT with patient’s disease status according to histology. Moreover, the immune responses of eradicated individuals from two different populations were analysed. Their immune response frequencies and intensities against all antigens except CagA declined below the detection limit. CagA was particularly long lasting in both independent populations. An isolated CagA band often represents past eradication with a likelihood of 88.7%. In addition, a high recomLine score was significantly associated with high-grade gastritis, atrophy, intestinal metaplasia, and gastric cancer. Thus, the recomLine is a sensitive and specific noninvasive test for detecting serum responses against H. pylori in actively infected and eradicated individuals. Moreover, it allows stratifying patients according to their disease state.